Tropical Africa : : Further correspondence (July 1919-December 1920) relating to medical and sanitary matters in tropical Africa - Great Britain Colonial Office; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1921)
Colonial Office file containing correspondence on health and medical administration, followed by: Papers relating to the revision of salaries in the East African dependencies; and, Visit of the [South African] Governor-General to the South West Territory in October 1919